The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1371/journal.pone.0207196
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fiber sources and non-starch polysaccharide-degrading enzymes modify mucin expression and the immune profile of the swine ileum

Abstract: Due to their complex chemical and physical properties, the effects and mechanisms of action of natural sources of dietary fiber on the intestine are unclear. Pigs are commonly fed high-fiber diets to reduce production costs and non-starch polysaccharide (NSP)-degrading enzymes have been used to increase fiber digestibility. We evaluated the expression of mucin 2 (MUC2), presence of goblet cells, and ileal immune profile of pigs housed individually for 28 days and fed either a low fiber diet based on corn-soybe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…Moreover, trans‐EKODE‐(E)‐Ib (also called 12,13‐epoxy‐9‐keto‐10‐trans‐octadecenoic acid) could be related to the inflammation regulation (Vangaveti, Jansen, Kennedya, & Malabu, 2016). As the production of MUC2 was closely associated with immunocytokine (Ferrandis Vila et al., 2018), these four metabolites that had immune‐modulatory function were potential substances enhancing MUC2. But the function of the remaining metabolite (1‐Hydroxytetrahydrocannabinol) is still unknown.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, trans‐EKODE‐(E)‐Ib (also called 12,13‐epoxy‐9‐keto‐10‐trans‐octadecenoic acid) could be related to the inflammation regulation (Vangaveti, Jansen, Kennedya, & Malabu, 2016). As the production of MUC2 was closely associated with immunocytokine (Ferrandis Vila et al., 2018), these four metabolites that had immune‐modulatory function were potential substances enhancing MUC2. But the function of the remaining metabolite (1‐Hydroxytetrahydrocannabinol) is still unknown.…”
Section: Resultsmentioning
confidence: 99%
“…TEER measurement and analysis of apical-to-basal transport of fluorescent probes indicated that 2D monolayer of pig, rabbit and bovine organoid cells is an efficient model to study paracellular epithelial permeability [ 16 , 19 , 23 ] (Figure 4 D, Additional file 1 ). Mucin 2, the main gel-forming mucin secreted by goblet cells, is expressed by intestinal organoids from pig, rabbit, horse and cows [ 16 , 19 23 , 25 , 27 , 43 ] (Figure 4 E and F). Expression of antimicrobial peptides or Paneth cell markers (REG3G, LYZ) was also detected in pig, horse, cow and rabbit organoids [ 16 , 19 , 22 , 25 , 39 ].…”
Section: Phenotype Of Livestock Intestinal Organoidsmentioning
confidence: 99%
“…Ferrandis et al used porcine and murine enteroids to study the role of cytokines (like interleukins (IL)-1β and IL-4) in the regulation of mucin production (i.e. expression of the MUC2 gene) by the epithelium, as dietary fiber and fiber-degrading enzymes in pig feed are known to affect expression of cytokines in the gut [ 74 ]. They found different effects of interleukins in porcine and murine enteroids, which shows the importance of using species-specific in vitro models for the target animal species.…”
Section: Research In Major Livestock and Companion Animalsmentioning
confidence: 99%